Comparison of specimen adequacy and diagnostic accuracy of a 25-gauge and 22-gauge needle in endobronchial ultrasound-guided transbronchial needle aspiration - Di Felice, Christopher; Young, Benjamin; Matta, Maroun (Journal of Thoracic Disease, 2019)
Background: Endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) is the preferred diagnostic modality for sampling mediastinal and hilar lymph nodes (LNs). The conventional needle used for sampling is either a 21-gauge (21G) or 22-gauge (22G). A 25-gauge (25G) needle has recently been introduced with little known regarding its efficacy. Methods: A retrospective study was conducted on patients referred for EBUS-TBNA who had LNs sampled using a 25G or 22G needle. A propensity score matching analysis was performed. After matching the groups, each LN was assessed for adequacy and final diagnosis. Non-diagnostic and benign lymphoid specimens were compared with repeat biopsy findings or long-term clinical and radiological follow-up. Results: A total of 158 LNs were included. An adequate sample was obtained in 92.4% (73/79) in the 25G group and 92.4% (73/79) in the 22G group (P=1). The 25G group diagnosed benign lymphoid tissue in 82.3% (65/79), granuloma in 7.6% (6/79) and malignancy in 2.5% (2/79). Six lymph nodes in the 25G group were non-diagnostic (7.6%). The 22G group diagnosed benign lymphoid tissue in 83.5% (66/79), granuloma in 3.8% (3/79) and malignancy in 5.1% (4/79). Six lymph nodes in the 22G group were non-diagnostic (7.6%). The sensitivity, specificity, negative predictive value (NPV) and diagnostic accuracy in the 25G group was 88.9% (95% CI, 51.8–99.7%), 100% (95% CI, 92.1–100%), 97.8% (95% CI, 87.6–99.7%) and 98.2% (95% CI, 90.1–100%), respectively. The sensitivity, specificity, NPV and diagnostic accuracy in the 22G group was 77.8% (95% CI, 40–97.2%), 100% (95% CI, 86.8–100%), 92.9% (95% CI, 79.3–97.8%) and 94.3% (95% CI, 80.8–99.3%), respectively. The 25G and 22G group were comparable in diagnostic accuracy (P=0.7). Conclusions: The 25G and 22G needle achieve comparable specimen adequacy and diagnostic accuracy in EBUS-TBNA.